2015
DOI: 10.1517/17425255.2015.1028355
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of uridine diphosphate glucuronosyltransferases

Abstract: Posttranscriptional regulation of UGTs has traditionally received less attention than nuclear regulation, in part because mechanisms involving ribosomes and endoplasmic reticula are challenging to investigate. Most promising of the posttranscriptional mechanisms reviewed are likely to be effects on co-substrate (UDP-glucuronic acid) transport and availability and structure-function changes to UGT proteins through, for example, glycosylation and phosphorylation. Although classical biochemistry continues to illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 129 publications
(137 reference statements)
0
14
0
Order By: Relevance
“…Nevertheless, based on the model, FvUGT1 may have an extra pelargonidin binding site in addition to the catalytic site. It has been suggested that the allosteric regulation exists in a rat hepatic UDP-glucuronosyltransferase [ 44 46 ] and other mammalian UGTs (reviewed in [ 47 ]). In the case of rat hepatic UGT, ATP and NADP + etc.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, based on the model, FvUGT1 may have an extra pelargonidin binding site in addition to the catalytic site. It has been suggested that the allosteric regulation exists in a rat hepatic UDP-glucuronosyltransferase [ 44 46 ] and other mammalian UGTs (reviewed in [ 47 ]). In the case of rat hepatic UGT, ATP and NADP + etc.…”
Section: Discussionmentioning
confidence: 99%
“…UGTs are glycoproteins resident of the endoplasmic reticulum (ER) membranes that undergo post-translational modifications (PTM) such as glycosylation and phosphorylation (Mackenzie 1990, Chakraborty et al 2012, Riches and Collier 2015. This family of proteins are involved in drug metabolism, accounting for approximately 55% of the 200 most prescribed drugs (Guillemette et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation affects the activity of many enzymes through increased interaction with a partner protein [38, 39], inhibition of intramolecular interaction [40, 41], decreased ability to be modified by ubiquitination and subsequent degradation [42, 43] and/or through altered access to the substrate [44, 45]. We previously showed that ALDH2 is a substrate of εPKC and that εPKC-mediated phosphorylation of ALDH2 leads to enhanced catalytic activity towards oxidation of toxic aldehydic substrate and confers cardioprotection against ischemia-reperfusion injury [31].…”
Section: Discussionmentioning
confidence: 99%